Benzyldimethyldodecyl Ammonium Chloride-Doped Denture-Based Resin: Impact on Strength, Surface Properties, Antifungal Activities, and In Silico Molecular Docking Analysis - Sarah Aldulaijan; Raghad Alruwili; Rawan Almulaify; Fatimah A. Alhassan; Yousif A. Al-Dulaijan; Faris A. Alshahrani; Lamia Mokeem; Mohammed M. Gad; Mary Anne S. Melo; Abdulrahman A. Balhaddad (Journal of Functional Biomaterials, 2024)
Candida albicans (C. albicans) adhering to denture-based resins (DBRs) is a known cause of denture stomatitis. A new approach to prevent denture stomatitis is to include antimicrobial substances within DBRs. Here, we examined the mechanical performance and antifungal properties of DBRs containing benzyldimethyldodecyl ammonium chloride (C12BDMA-Cl) as an antimicrobial compound. C12BDMA-Cl is a quaternary ammonium compound, and its antifungal properties have never been investigated when combined with dental acrylic resin. Therefore, we modified a commercially available heat-polymerized acrylic DBR to contain 3 and 5 wt.% of C12BDMA-Cl. Unmodified DBR was used as a control group. Specimens were prepared using the conventional heat processing method. The specimen’s flexural strength, elastic modulus, microhardness, and surface roughness were evaluated. C. albicans biofilm was grown on the specimens and assessed via colony-forming units (CFUs) and scanning electron microscopy (SEM). In silico molecular docking was applied to predict the potential C12BDMA-Cl inhibition activity as an antifungal drug. The 3% C12BDMA-Cl DBR demonstrated antifungal activities without a deterioration effect on the mechanical performance. SEM images indicated fewer colonies in DBR containing C12BDMA-Cl, which can be a potential approach to managing denture stomatitis. In conclusion, C12BDMA-Cl is a promising antifungal agent for preventing and treating denture stomatitis.